Curriculum development : a guide to practice - Wiles, Jon.; Bondi, Joseph C. (New York : Pearson, 2015)
This edition identifies 25 individual strategies, currently used worldwide, for promoting educational development, strategies that schools, districts, states, and nations will employ in transforming their systems for the new global age. While maintaining its established, well-known focus on historical and philosophical aspects of curriculum development, this edition also includes updated chapters on technology, the Common Core movement, and the curriculum activities of the world's leading nations, along with practical applications of these historic and novel principles of curriculum work.
Includes bibliographical references and indexes.
Keywords: Curriculum planning -- United States; Education -- Curricula -- United States